Luc Tuymans : Graphic works, 1989-2012 - Sellink, Manfred; Simoens, Tommy (Antwerpen : Ludion, 2012)
Catalogue raisonné, offering a retrospective of more than twenty years of graphic works in various techniques, from photocopy to serigraph on monotype, lithograph, aquatint, photogravure, in situ projects and installations. Using unpublished source material and proofs, polaroids and watercolours--some from the archives of the master printer Roger Vandaele and the artist's own studio. An illustrated survey of Tuymans' complete graphic work from 1989 to 2012.
boek
Keywords: Tuymans, Luc